Sex Differences in the Prevalence of Diastolic Dysfunction in Cardiac Surgical Patients. Issue 3 (9th January 2015) - Ferreira, Renata G.; Worthington, Andrea; Huang, Chuan‐Chin; Aranki, Sary F.; Muehlschlegel, Jochen D.
Abstract Objectives The mortality from diastolic dysfunction is approximately 9% to 28%. In patients with ischemic heart disease, female sex and advanced age are associated with increases in ventricular diastolic stiffness. Clinical studies have found higher rates of diastolic dysfunction in women, despite higher ejection fractions, than in men post–myocardial infarction. Therefore, we hypothesized that female patients undergoing cardiac surgery have higher degrees of diastolic dysfunction and experience more adverse outcomes, such as prolonged hospitalization. Methods We prospectively enrolled 153 patients undergoing cardiac surgery. Diastolic function was assessed using early transmitral velocity (E) and early diastolic lateral mitral annular tissue velocity (e'). Left ventricular diastolic dysfunction was defined as binary and a continuous outcome (E/e'). Results Females were more likely than males to present with higher E/e' (11.5 vs. 7.9, p = 0.001) and higher left ventricular diastolic dysfunction (71% vs. 36%, p < 0.001). The addition of sex to the model for left ventricular diastolic dysfunction was significant. The relationship between sex and E/e' ratio showed the biggest difference between males and females in the 56–72‐year‐old age brackets, where women were much more likely to have a higher E/e' than males. Conclusions We identified a significantly higher prevalence of diastolic dysfunction among females presenting for elective cardiac surgery compared to males. This finding is more pronounced with age. Additionally, we found that female sex is at higher risk of prolonged ICU and hospital length of stay. doi: 10.1111/jocs.12506 (J Card Surg 2015;30:238–245)